2018
DOI: 10.3389/fphys.2018.00070
|View full text |Cite
|
Sign up to set email alerts
|

PVAT and Its Relation to Brown, Beige, and White Adipose Tissue in Development and Function

Abstract: Adipose tissue is commonly categorized into three types with distinct functions, phenotypes, and anatomical localizations. White adipose tissue (WAT) is the major energy store; the largest depots of WAT are found in subcutaneous or intravisceral sites. Brown adipose tissue (BAT) is responsible for energy dissipation during cold-exposure (i.e., non-shivering thermogenesis) and is primarily located in the interscapular region. Beige or brite (brown-in-white) adipose tissue can be found interspersed in WAT and ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
84
0
6

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(102 citation statements)
references
References 113 publications
(175 reference statements)
1
84
0
6
Order By: Relevance
“…Our study has also revealed that MRPVAT and RP fat are rich in macrophages and T cells while APVAT and SS fat are T cell rich. Gene and protein expression studies from other labs reveal striking similarities between thoracic aortic PVAT and classical interscapular brown adipose tissue in mice (Fitzgibbons et al, 2011;Hildebrand et al, 2018) that are significantly different from WAT. This aligns well with our current findings and suggests that MRPVAT may be functionally similar to its respective non-PVAT RP fat, but different from APVAT.…”
Section: Discussionmentioning
confidence: 91%
“…Our study has also revealed that MRPVAT and RP fat are rich in macrophages and T cells while APVAT and SS fat are T cell rich. Gene and protein expression studies from other labs reveal striking similarities between thoracic aortic PVAT and classical interscapular brown adipose tissue in mice (Fitzgibbons et al, 2011;Hildebrand et al, 2018) that are significantly different from WAT. This aligns well with our current findings and suggests that MRPVAT may be functionally similar to its respective non-PVAT RP fat, but different from APVAT.…”
Section: Discussionmentioning
confidence: 91%
“…While WAT derives from a distinct cell lineage and is predominantly made up of white adipocytes, it also contains brown-like cells, called beige or brite adipocytes. Beige adipocytes are a distinct thermogenic fat cell type from brown adipocytes; they derive from the same lineage as white adipocytes and form sporadic pockets within WAT (27)(28)(29)(30)(31). Beige adipogenesis is induced under a variety of conditions such as cold, caloric restriction, and exercise (27)(28)(29).…”
Section: Humans May Have Lower Beiging Potential Than Chimpanzeesmentioning
confidence: 99%
“…Beige adipocytes are a distinct thermogenic fat cell type from brown adipocytes; they derive from the same lineage as white adipocytes and form sporadic pockets within WAT (27)(28)(29)(30)(31). Beige adipogenesis is induced under a variety of conditions such as cold, caloric restriction, and exercise (27)(28)(29). Although beige adipocytes stem from the same lineage as white adipocytes, beige cells share characteristics of classical brown fat, such as higher numbers of mitochondria and smaller but more numerous lipid droplets (28).…”
Section: Humans May Have Lower Beiging Potential Than Chimpanzeesmentioning
confidence: 99%
“…For many decades, adipose tissue has been considered as an energy store where excess carbohydrates and fatty acids are stored in the form of lipids. In recent years, it has emerged that fat tissue has a wide range of other paracrine, endocrine, and immune functions [1][2][3]. Furthermore, there are different types of adipose tissue that are located at distinct anatomical locations [1][2][3].…”
Section: Introductionmentioning
confidence: 99%